Mapping N2O production pathways in estuarine and coastal sediments through coupled 15N tracing and N2O isotopocules analysis - Chen, Cheng; Yin, Tianyu; Yin, Guoyu; Liang, Xia; Li, Xiaofei; Hou, Lijun; Liu, Min (Journal of hydrology (Amsterdam), 2024)
[Display omitted] •N2O sources and dynamics in estuarine sediments were comprehensively mapped.•N2O production pathways exhibited greater spatial than season variability.•Denitrification ruled N2O production over autotrophic and heterotrophic nitrification.•Bacterial and fungal denitrification showed contrasting patterns of contribution.•Microecology theory revealed the regulatory mechanisms of N2O production pathways. Estuarine and coastal zones are important sources of atmospheric nitrous oxide (N2O). Previous studies have explored the overarching roles of nitrification and denitrification in N2O production from these critical zones, yet the specific productions of various pathways within these processes remain elusive. Using dual 15N tracers (15NH4+ and 15NO3-) coupled with N2O isotopocules analysis, we quantified the contributions of multiple nitrification (both autotrophic and heterotrophic) and denitrification (bacterial, fungal, and chemical) pathways to N2O production in estuarine and coastal sediments. Furthermore, we leveraged microecology theory to dissect the biogeochemical mechanisms that govern the spatiotemporal dynamics of these pathways. Results showed that denitrification was the dominant process, accounting for over 70 % of N2O production. The remainder was attributed to autotrophic nitrification (5.80–23.92 %) and heterotrophic nitrification (1.07–7.10 %). Isotopocules analyses further showed that fungal denitrification was the primary source at freshwater sites (40.47–49.99 %), whereas bacterial denitrification prevailed at high-salinity sites (51.37–52.55 %). Moreover, these processes displayed contrasting spatial variability along the estuarine salinity gradient. Mechanistic investigation informed by microecology theory demonstrated that distinct assembly processes governed bacterial and fungal communities across this gradient, resulting in divergent ecological adaptation strategies of bacterial and fungal denitrifiers and, consequently, the contrasting contribution patterns of bacterial and fungal denitrification. Collectively, our work presents a comprehensive and refined picture of N2O sources and dynamics, offering essential insights for improving predictive models and formulating effective mitigation strategies targeting N2O emissions from estuarine and coastal zones.